Creatividad y su influencia en el desarrollo de la psicomotricidad fina en niños de Educación Inicial I - Barrió Banchón, Génesis Arelys (2025)
Creativity develops important aspects in students such as development, imagination and other factors that need to be developed by students, when developing fine motor activities, the ability to concentrate, hand-eye coordination and movement control are stimulated. Not all children manage to understand the activities or games that the teacher performs, which may be because the teacher is not correctly applying strategies that promote creativity, which is significantly limiting the development of fine psychomotor skills, which is why the main objective of this research is to analyze the influence of creativity in the development of creativity, which is followed by the qualitative approach, using the non-experimental design since it is not intended to intervene in the study variables, as a technique for collecting information, an interview and observation form were carried out, which was applied to two teachers in the area of Initial Education I, and 25 children in parallel "A", followed by its measuring instrument such as the open question questionnaire and an observation form. The final result shows that creativity and fine motor skills are very important aspects that can be developed in different ways in Early Childhood Education, as teachers promote creativity through reading stories and free drawing, and by carrying out these activities, fine motor skills are also benefited. In conclusion, creativity acts as an important driver in the development of fine motor skills, allowing for learning and enhancing imagination through activities such as drawing and painting.